Modular total synthesis of (+/-)-trigonoliimine C - Reddy, B. Narendraprasad; Ramana, Chepuri V. (Chemical Communications, 2013)
A convergent total synthesis of trigonoliimine C has been executed by employing three catalytic transformations in sequence. The key reactions that have been developed in this context include the [Au]-catalyzed addition of protected tryptamine to isatogens and the reduction of N-OH to NH with hydrazine monohydrate.